Interphase investigation of modified McLachlan model and the 3D finite element method for electrical conductivity - Muhammad Zulkarnain; Irianto Harny; A.A.M. Damanhuri (Heliyon)
This paper explores the electrical conductivity interphase of Ag/Epoxy composite using modified McLachlan theory and 3D finite element composite model through experimental verification. The model characteristic presents conductivity as a dynamic function influenced by particle content, particle electrical properties, electrical properties transition, and an exponent. This model was meticulously crafted, considering the intricate interplay between the polymer matrix and silver particles, the tunnelling distance between adjacent silver particles, and the interphase regions around particles. This model has proven its mettle through rigorous analysis of experimental results and the impact of various parameters on conductivity. The predictions have shown impressive alignment with the experimental data, highlighting the crucial roles played by the parameters in the conductivity of silver composites where the percolation threshold reached 6 vol % of filler loading. The experimental study demonstrated that the electrical conductivity was 3.84 × 10−1 S/cm for micro-sized particles and 1.32 × 10−2 S/cm for nano-sized particles. Notably, a large tunnelling distance drastically reduces conductivity, while higher and slighter surface energies of the polymer matrix and filler enhance conductivity. Furthermore, a thin interphase yields minimal conductivity, whereas a thick interphase and low waviness improve conductivity. The McLachlan-modified model falls slightly short in accuracy compared to the 3D finite element method models. Adjustments to the equations can enhance its alignment with experimental data.